Electronic nose: A useful tool for monitoring environmental contamination - Baby, Rosa Elisa (2000)
The advances in the technology of multisensor arrays and neural computation have allowed the development of 'electronic noses', which has enabled the discrimination of compounds by their odours and consequently, has played a fundamental role in the environmental monitoring. An electronic nose MOSES II (MOdular SEnsor System) with two arrays of eight (tin oxide and quartz microblance) sensors, each one manufactured by Lennartz Electronic/MoTech, was employed in this work. The aim of this research was to discriminate the following factors by odours: (a) small concentrations (ppm) of lindane and nitrobenzene in water, (b) dry solid insecticides (synthetic pyrethroids) such as permethrin, deltamethrin and cypermethrin, © mixtures of different quantities of cypermethrin in an inert substance, and (d) solutions of these pyrethroids in an appropriate organic solvent. Contaminating residues of insecticides (lindane and synthetic pyrethroids) and products from the leather manufacture (phenols, nitrobenzene, anilines) are often offloaded into streams or rivers-despite the prohibition regulations-in heedless disregard of the danger they present to the health of the population and the survival of fish and flora.